Ethics and Governance of AI in Education: Balancing Innovation and Accountability - Komarudin Komarudin (International Journal of Social Research, 2025)
The integration of artificial intelligence (AI) in education has presented great opportunities for innovation, such as personalized learning, adaptive assessment, and administrative efficiency. However, these developments also pose ethical and governance challenges, especially related to data privacy, algorithmic bias, transparency, and the risk of increasing education gaps. This research aims to critically examine how ethical and governance principles can be designed to balance the benefits of AI innovation with the need for responsible accountability. The research method uses qualitative analysis of global policy documents, AI guidelines from UNESCO and OECD, and institutional case studies, complemented by semi-structured interviews with education and technology experts. The results show that although AI has great potential to transform pedagogical practices, existing governance mechanisms are still fragmented and have not been consistently implemented. The main gaps identified include low ethical literacy among educators, weak institutional accountability structures, and the absence of harmonized global policies. The contribution of this research is to propose a conceptual model of AI governance in education that integrates the principles of transparency, fairness, and accountability with innovation strategies. This model offers a direction for policymakers, institutions, and educators to use AI responsibly while safeguarding human values, thereby strengthening the discourse on the ethical use of AI in education.